An Efficient Approach to Optimize the Performance of Massive Small Files in Hadoop MapReduce Framework - Guru Prasad, MS; Nagesh, HR; Prabhu, Swathi (International Journal of Computer Sciences and Engineering, 2025)
The most popular open source distributed computing framework called Hadoop was designed by Doug Cutting and his team, which involves thousands of nodes to process and analyze huge amounts of data called Big Data. The major core components of Hadoop are HDFS (Hadoop Distributed File System) and MapReduce. This framework is the most popular and powerful for store, manage and process Big Data applications. But drawback with this tool related to stability and performance issues for small file applications in storage, manage and processing the data. Existing approaches deals with small files problem are Hadoop archives and SequenceFile. However, existing approaches doesn’t give an optimized performance to solve small files problems on Hadoop. In order to improve the performance in storing, managing and processing small files on Hadoop, we proposed an approach for Hadoop MapReduce framework to handle the small files applications. Experimental result shows that proposed framework optimizes the performance of Hadoop in handling of massive small files as compared to existing approaches.